Ministry Of Finance Decree No. 217 of the Year 2020 Amending Certain Provisions of the Executive Regulations of the Income Tax Law, As Issued by Minister of Finance's Decree No. 991 of the Year 2005 = وزارة المالية قرار رقم 217 لسنة 2020 بتعديل بعض احكام اللائحة التنفيذية لقانون الضريبة على الدخل الصادرة بقرار وزير المالية رقم 991 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic